A LETTER FROM GOD INTENDED FOR THE GENERAL PUBLIC. Issue 53 (2019) - Unknown
Abstract : In this letter to the general public, received by Think some time ago, God complains that the growth of science has made it progressively more difficult to communicate with everyone as much as he would like. He then apologizes for not anticipating that scientific explanations would always be preferable to appeals to miracles in accounting for strange or unusual phenomena.